Fluorine Modified Boron Carbon Nitride Semiconductors for Improved Photocatalytic CO2 Reduction under Visible Light. Issue 22 (24th October 2018) - Xing, Fangshu; Liu, Qiuwen; Song, Mingxia; Huang, Caijin
Abstract: Photocatalytic conversion of CO2 to usable fuel precursors is one of the most important renewable paths to mitigate energy shortages and greenhouse gas emissions. Photocatalysts for this transformation are typically based on precious metals to obtain high yield and selectivity. Currently, metal‐free graphitic conjugated materials (such as g‐C3 N4, ternary boron carbon nitride) are promising and emerging photocatalysts to offset the above issues. Here we further modulated photocatalytic performance of ternary boron carbon nitride (BCN) by introducing fluorine into its graphitic‐like framework. As a result, the fluorination of the BCN productively increases the CO yield by three times under visible light. It was found that fluorine doping can remarkably accelerate migration‐separation efficiency of photogenerated charge carriers, prolong lifetime of the excited state and optimize electronic properties of BCN. Abstract : Be a boron ! Boron carbon nitride ternary (BCN) is promising and emerging metal‐free visible light‐driven conjugated photocatalysts. Here, fluorine‐doped BCN (BCN−F) was rationally designed and applied in photocatalytic CO2 conversion in MeCN/H2 O/TEOA system under visible light. The as‐obtained BCN−F photocatalysts exhibited enhanced CO2 ‐to‐CO conversion activity and high stability due to optimized electronic properties, accelerated charge transfer‐separation efficiency and prolonged lifetime of the excited state.